Fetal and Postnatal Magnetic Resonance Imaging of Unilateral Cystic Renal Dysplasia in a Neonate with Tuberous Sclerosis - Vineet Tyagi; Eran Bornstein; Robert Schacht; Shailee Lala; Sarah Milla (Elsevier, 2016)
Tuberous sclerosis (TS) is an autosomal dominant condition associated with mutations in the TSC1 and/or TSC2 genes. Clinical manifestations are multisystemic, and they often include lesions in the brain, skin, heart, kidneys, and bones. TSC2 gene mutations can be seen concomitantly with autosomal dominant polycystic kidney disease gene mutations. We present a case of a fetus with prenatal diagnosis of TS that had unique asymmetrical distribution of renal cystic disease. We describe the extensive work up with both fetal and neonatal magnetic resonance imaging with correlating images of the unilateral polycystic renal disease in addition to typical TS brain findings.